Income Poverty in Argentina and Bahía Blanca: Reference estimates and methodological issues (Actualidad Económica, 2016)
In this paper we estimate the indigence and poverty by income in 2014 and 2015 for the total urban agglomera-tions of Argentina and for the particular case of Bahía Blanca, an intermediate city, eminently industrial and com-mercial, with high levels of recent unemployment and indigence. It is found that by the middle of 2015 one in ten people was in a situation of indigence and almost three out of ten were in poverty, which is equivalent to approxi-mately 11.6 million people. In the case of the Bahía Blanca agglomerate, one in 20 people were indigent, and 18% were poor, which translates into 15,000 and 54,000 people living in extreme poverty and poverty. The paper also presents some critical points of the methodology for measuring poverty by income that require reflection and im-provement in the process of restitution of official poverty statistics.